Implementation of new physics models for low energy electrons in liquid water in Geant4-DNA. Issue 12 (December 2016) - Bordage, M.C.; Bordes, J.; Edel, S.; Terrissol, M.; Franceries, X.; Bardiès, M.; Lampe, N.; Incerti, S.
Highlights: Implementation of electron cross sections for liquid water from CPA100 code. Verification of the implementation against the original CPA100 code. Comparison of cross sections, range, number of interactions and dose point kernels. Abstract: A new alternative set of elastic and inelastic cross sections has been added to the very low energy extension of the Geant4 Monte Carlo simulation toolkit, Geant4-DNA, for the simulation of electron interactions in liquid water. These cross sections have been obtained from the CPA100 Monte Carlo track structure code, which has been a reference in the microdosimetry community for many years. They are compared to the default Geant4-DNA cross sections and show better agreement with published data. In order to verify the correct implementation of the CPA100 cross section models in Geant4-DNA, simulations of the number of interactions and ranges were performed using Geant4-DNA with this new set of models, and the results were compared with corresponding results from the original CPA100 code. Good agreement is observed between the implementations, with relative differences lower than 1% regardless of the incident electron energy. Useful quantities related to the deposited energy at the scale of the cell or the organ of interest for internal dosimetry, like dose point kernels, are also calculated using these new physics models. They are compared with results obtained using the well-known Penelope Monte Carlo code.